Delta opioid receptor on equine sperm cells: subcellular localization and involvement in sperm motility analyzed by computer assisted sperm analyzer (CASA) - Lacalandra Giovanni M; Albrizio Maria; Micera Elisabetta; Guaricci Antonio C; Nicassio Michele; Zarrilli Antonia (BMC, 2010)
Abstract Background Opioid receptors and endogenous opioid peptides act not only in the control of nociceptive pathways, indeed several reports demonstrate the effects of opiates on sperm cell motility and morphology suggesting the importance of these receptors in the modulation of reproduction in mammals. In this study we investigated the expression of delta opioid receptors on equine spermatozoa by western blot/indirect immunofluorescence and its relationship with sperm cell physiology. Methods We analyzed viability, motility, capacitation, acrosome reaction and mitochondrial activity in the presence of naltrindole and DPDPE by means of a computer assisted sperm analyzer and a fluorescent confocal microscope. The evaluation of viability, capacitation and acrosome reaction was carried out by the double CTC/Hoechst staining, whereas mitochondrial activity was assessed by means of MitoTracker Orange dye. Results We showed that in equine sperm cells, delta opioid receptor is expressed as a doublet of 65 and 50 kDa molecular mass and is localized in the mid piece of tail; we also demonstrated that naltrindole, a delta opioid receptor antagonist, could be utilized in modulating several physiological parameters of the equine spermatozoon in a dose-dependent way. We also found that low concentrations of the antagonist increase sperm motility whereas high concentrations show the opposite effect. Moreover low concentrations hamper capacitation, acrosome reaction and viability even if the percentage of cells with active mitochondria seems to be increased; the opposite effect is exerted at high concentrations. We have also observed that the delta opioid receptor agonist DPDPE is scarcely involved in affecting the same parameters at the employed concentrations. Conclusions The results described in this paper add new important details in the comprehension of the mammalian sperm physiology and suggest new insights for improving reproduction and for optimizing equine breeding.